Evaluating the quality-of-life for patient surviving with breast cancer diseases - Abdul Aziz, Nor Intan Shamimi; Ali, Mass Hareeza; Jamil, Ahmad Taufik; Ab Aziz, Yuhanis (Taylor and Francis, 2025)
Background: Breast cancer's prevalence and mortality are concerning, with 8,418 women diagnosed in Malaysia in 2020. It significantly impacts physical, mental, and emotional well-being, reducing overall quality of life. Aims: To understand the factors affecting the well-being of breast cancer survivors, it is crucial to examine psychological state, self-care behaviours, social support, healthcare support, and social media’s impact on quality of life. Inconsistent information on social media can pose risks, but it can also be used as an educational tool to improve quality of life. Methods: A pilot study assessed the psychometric instruments among 30 breast cancer survivors, using IBM SPSS Version 28 and SmartPLS4 for data analysis. Results: The survey instrument proved reliable for all five variables with Cronbach's alpha values: psychological state (0.896), self-care behaviour (0.922), social support (0.949), healthcare support (0.935), and social media (0.935). The self-care behaviour construct showed discriminant validity, with an average variance extracted (AVE) of 0.094. Some items from each construct were invalid, requiring modification. Conclusion: This pilot study established a reliable survey foundation, assessing critical factors in Malaysian breast cancer survivors. It identified areas for improvement and constraints like sample size, guiding future data collection. The study provides valuable insights for future research on their quality of life.